FOOD SECURITY AND SUSTAINABLE AGRICULTURE - Ixtiyorova Shahrizoda Qudrat qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation Food security is a critical issue that affects global changes in various ways. Food security refers to the condition in which all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for an active and healthy life.